Strategi PAILKEM dalam Pembelajaran Bahasa Arab bagi Anak Berkebutuhan Khusus: Ṭarīqah PAILKEM fī Ta’līm al-Lugah al-‘Arabiyyah Ladā al-Aṭfāl zāwi al-Iḥtiyājāt al-Khāssah - Aziz, Muhammad Tareh; Hasan, Laili Mas Ulliyah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The researcher carried out learning activities with Muhammad Syauqi as the research object. The researcher directly saw and observed how Muhammad Syauqi used language, which in learning mufrodat, the researcher used the PAILKEM strategy. This research uses a qualitative method with a case study type. In collecting data, researchers also used documentation and direct interviews with Muhammad Syauqi's mother as an informant (resource person). Qualitative data will be analyzed by researchers using a thematic analysis approach. Data organization, from interviews, observations, and document analysis will be organized and grouped based on general themes. The results of this research are the strategy used by the researcher using audiovisual stimuli in giving mufrodat, then the researcher gives a word guessing game, the researcher only uses vocabulary that he already knows in his first language. After that, researchers saw that Syauqi could also compose simple words by himself, both orally and in writing. The strategy implemented by the researcher was very effective in cultivating the spirit of Syauqi, but there were several obstacles found by the researcher, namely, there were several Arabic vocabulary words that were easy to pronounce, while those with repetition were difficult to pronounce, so the researcher concluded that there were several levels in the pronunciation of vocabulary for children. down syndrome. However, the solution to this obstacle is to provide intervention and treatment to Syauqi to increase his fluency and sharpness in pronouncing Arabic vocabulary.